2022
DOI: 10.1038/s41531-022-00405-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin and T2*-MRI for the assessment of genetically at-risk, prodromal, and symptomatic Parkinson’s disease

Abstract: MRI was suggested as a promising method for the diagnosis and assessment of Parkinson’s Disease (PD). We aimed to assess the sensitivity of neuromelanin-MRI and T2* with radiomics analysis for detecting PD, identifying individuals at risk, and evaluating genotype-related differences. Patients with PD and non-manifesting (NM) participants [NM-carriers (NMC) and NM-non-carriers (NMNC)], underwent MRI and DAT-SPECT. Imaging-based metrics included 48 neuromelanin and T2* radiomics features and DAT-SPECT specific-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Du Guangwei et al also mentioned in the study that during the 18 months follow-up, the substantia nigra pars compacta R2 * showed a faster increase in PD compared with controls. Through ROC curve analysis, we found that the average value of R2 * in the right substantia nigra compact zone has higher diagnostic energy efficiency, in line with previous results ( 2 , 20 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…Du Guangwei et al also mentioned in the study that during the 18 months follow-up, the substantia nigra pars compacta R2 * showed a faster increase in PD compared with controls. Through ROC curve analysis, we found that the average value of R2 * in the right substantia nigra compact zone has higher diagnostic energy efficiency, in line with previous results ( 2 , 20 , 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…The findings indicated genotype-specific differences in NM-based radiomic features only. Specifically, significant differences in the left and NM-SN skewness radiomic feature between sPD were observed, possibly indicating greater dopaminergic loss in the LRRK2 -PD group [ 26 ].…”
Section: Imaging Studies Findings In Genetic Forms and Prodromal Phas...mentioning
confidence: 99%
“…Another study reported significantly lower T2*‐based contrast in the left red nucleus in patients with GBA‐PD compared with those having iPD. However, no significant differences in the neuromelanin signal in the substantia nigra were found between GBA‐PD and iPD groups 9 . Collectively, these findings motivated us to investigate white matter (WM) alterations.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant differences in the neuromelanin signal in the substantia nigra were found between GBA-PD and iPD groups. 9 Collectively, these findings motivated us to investigate white matter (WM) alterations. WM microstructure abnormalities have been widely observed using diffusion tensor imaging (DTI) in patients with iPD.…”
Section: Introductionmentioning
confidence: 99%